Projecting the Global Potential Geographical Distribution of Ceratitis capitata (Diptera: Tephritidae) under Current and Future Climates - Jiawei Rao; Yu Zhang; Haoxiang Zhao; Jianyang Guo; Fanghao Wan; Xiaoqing Xian; Nianwan Yang; Wanxue Liu (Biology, 2024)
The Mediterranean fruit fly, Ceratitis capitata (Wiedemann), which is native to tropical Africa, has invaded more than 100 countries and constitutes a risk to the citrus sector. Studying its potential geographical distribution (PGD) in the context of global climate change is important for prevention and control efforts worldwide. Therefore, we used the CLIMEX model to project and assess the risk of global invasion by C. capitata under current (1981–2010) and future (2040–2059) climates. In the prevailing climatic conditions, the area of PGD for C. capitata was approximately 664.8 × 105 km2 and was concentrated in South America, southern Africa, southern North America, eastern Asia, and southern Europe. Under future climate conditions, the area of PGD for C. capitata is projected to decrease to approximately 544.1 × 105 km2 and shift to higher latitudes. Cold stress was shown to affect distribution at high latitudes, and heat stress was the main factor affecting distribution under current and future climates. According to the predicted results, countries with highly suitable habitats for C. capitata that have not yet been invaded, such as China, Myanmar, and Vietnam, must strengthen quarantine measures to prevent the introduction of this pest.